Dog sense ebook How the new science of dog behavior can make you a better friend to your pet. - Bradshaw, John (2012)
Dogs have been mankind's faithful companions for tens of thousands of years, yet today they are regularly treated as either pack-following wolves or furry humans. The truth is, dogs are neither — and our misunderstanding has put them in serious crisis. What dogs really need is a spokesperson, someone who will assert their specific needs. Renowned anthrozoologist Dr. John Bradshaw has made a career of studying human-animal interactions, and in Dog Sense he uses the latest scientific research to show how humans can live in harmony with — not just dominion over — their four-legged friends. From explaining why positive reinforcement is a more effective (and less damaging) way to control dogs' behavior than punishment to demonstrating the importance of weighing a dog's unique personality against stereotypes about its breed, Bradshaw offers extraordinary insight into the question of how we really ought to treat our dogs.